2015
DOI: 10.5888/pcd12.140400
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Healthy Food Options on Children’s Menus of Restaurants in the Health-Disparate Dan River Region of Virginia and North Carolina, 2013

Abstract: IntroductionInterest has increased in understanding the types and healthfulness of restaurant foods for children, particularly in disadvantaged areas. The purpose of this community-based participatory research study was to describe the quality of restaurant food offered to children in a health-disparate region in Virginia and North Carolina and to determine if the availability of healthy foods differed by location (rural, urban) or by the predominant race (black, white, mixed race) of an area’s population.Meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
16
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 27 publications
1
16
0
Order By: Relevance
“…To our knowledge, the present study is the first to investigate the children's restaurant FE in two cities on either side of the Canada-US border, and the first to develop and implement an index for neighbourhood restaurant quality in children (NRQI-C). Several studies have employed the CMA in various settings to examine the restaurant FE for children (11,22,(38)(39)(40)(41)(42)(43) , but virtually none go beyond descriptive results to analyse the relationship between FE and neighbourhood socio-economic characteristics. An exception is Hill et al (38) , who explored how children's menu scores differ in urban and rural areas, as well as by block group race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…To our knowledge, the present study is the first to investigate the children's restaurant FE in two cities on either side of the Canada-US border, and the first to develop and implement an index for neighbourhood restaurant quality in children (NRQI-C). Several studies have employed the CMA in various settings to examine the restaurant FE for children (11,22,(38)(39)(40)(41)(42)(43) , but virtually none go beyond descriptive results to analyse the relationship between FE and neighbourhood socio-economic characteristics. An exception is Hill et al (38) , who explored how children's menu scores differ in urban and rural areas, as well as by block group race/ethnicity.…”
Section: Discussionmentioning
confidence: 99%
“…28 These findings are not surprising, as foods marketed to children at restaurants are often high in energy density and low in micronutrient density. 29 It would be important to develop healthier eating-out alternatives for children and adolescents, but to combine health and attractiveness is obviously a great challenge. We did not find any associations between school lunch availability and dietary patterns.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies [ 53 , 54 , 55 , 56 , 57 , 58 , 59 , 60 , 61 ] revealed that between one and 13 percent of meals sold to children, adolescent and their parents met healthy criteria recommended by authoritative bodies. Kirkpatrick et al [ 53 ] ( n = 5 QSR chains) found that in 2006 children’s menu items scored higher than adult items, and those labeled “healthy or nutritious” had a higher HEI-2005 score than the full-menu items.…”
Section: Resultsmentioning
confidence: 99%
“…Krukowski et al [ 58 ] ( n = 130 local QSR chains and non-chains) found that only 13 percent of children′s menus provided healthy options between 2009 and 2010. Between 2012 and 2013, three studies [ 59 , 60 , 61 ] revealed that between one and 11 percent of children’s meals met recommended nutrition criteria.…”
Section: Resultsmentioning
confidence: 99%